(untitled) (AYUSHDHARA, 2022)
The COVID-19 pandemic has transferred the outlook of every individual toward materialistic things. After each departing day, there are some points for optimism and agony both. The Covid-19 has changed the mental makeup due to sudden lock down and crises in the economy. Researchers are doing their best to slow down this contagious disease. Slowly the recovery rate is also boosting up. Different pathy comes together to find the right solution somehow, symptomatic management is quite possible with integration. But, now a new challenge is approaching as post-recovery phase symptoms or follow-up symptoms which mainly include the psycho-physical conditions. Among the recovered individuals from infection of the corona, various mental symptoms like depression or stress are the most striking one. Different modules were functioning in both traditional and contemporary sciences for inner peace or reducing the psycho-physical symptoms. Based on different studies performed on various parameters makes the meditation most reliable. The present metanalysis is carried out to find the role of the meditation or Dhyana in managing the post- COVID psychological symptoms w.s.r to breathing practices. After completion of the study, it was found that the practice of meditation in post recovered persons will not only bring inner solace by reducing the physiological symptoms but will also reduce spending on health.